Investimento direto estrangeiro em infraestrutura de saneamento nos países emergentes - Silva, Pedro Augusto Godeguez da (2013)
Direct investment in the sanitation sector is a phenomenon that deserves attention due to these market failures, and therefore the regulation through public policies, among other variables of institutional character, in company decisions. This work aims to identify the determinants of the choice of destination countries among emerging countries, to direct investments in sanitation. Based on the theoretical framework that combines economic approaches to internationalization of companies with the microeconomics of industrial organization, also inserting elements of new institutional economics, specific hypotheses were generated regarding these determinants. Raise the hypotheses that foreign direct investment in sanitation in developing countries is related to the level of economic development, the existing infrastructure and institutional stability influences the choice of countries. To test the hypotheses, we propose an econometric approach, using a binary choice model (LOGIT) and to assess the dynamic effects, a model of LOGIT panel. Are used data from the PPI (Private Participation in Infrastructure), the World Bank and selected economic and institutional indicators, particularly on the institutional environment indices. As a result, in addition to confirming the proposed hypothesis, this study found a relationship of inverted "U" between per capita GDP and the likelihood of receiving direct investment in sanitation, suggesting a possible behavior of "crowding out" investment in some countries.